"Mzabalazo on the Move" : organising Workers on a Commuter Train in Tshwane -An Ethnographic Study of Mamelodi Train Sector - Bezuidenhout, Andries (University of Pretoria, 2018)
Thesis (DPhil)--University of Pretoria, 2018.